Research of process of abrasive wear of pin surfaces in the conditions of shock loading of work of beat of grinding down - Попов, Сергій Миколайович (Eastern-European Journal of Enterprise Technologies, 2013)
The article formulated the basic requirements for the chemical composition, structure-phase state and physical-mechanical properties of the material for parts, operating under conditions of wear by the half-fastened abrasive with local shock loads and jamming of particles. The aim of this work was to study and analyze the nature of the destruction of working objects – beaters of dispergators, and to develop recommendations as to the improvement of their operation life by optimization of technological operation factors and further development of the strengthening technology. It was found that the main mechanism of destruction of the dispersant working objects had been the multiple redeformation of same areas of the working surface. We will use the results of the study in future to develop the reinforcement wear-resistant material and technology of its application